EMPOWER: An Intervention to Address Barriers to Pain Management in Hospice - Cagle, John G.; Zimmerman, Sheryl; Cohen, Lauren W.; Porter, Laura S.; Hanson, Laura C.; Reed, David (Journal of pain and symptom management, 2015)
Concerns about pain medications are major barriers to pain management in hospice, but few studies have focused on systematic methods to address these concerns. The objective of this study was to test the preliminary efficacy of the Effective Management of Pain: Overcoming Worries to Enable Relief (EMPOWER) intervention, which included hospice staff education, staff screening of barriers to pain management at admission, and discussion about misunderstandings regarding pain management with family caregivers and patients. We conducted a pilot, cluster randomized, controlled trial with four hospices. One hundred twenty-six family caregivers (55 interventions and 71 controls) were interviewed at two weeks after admission. If patients survived three months after admission, caregivers were reinterviewed. At two weeks, caregivers in the intervention group reported better knowledge about pain management (P = 0.001), fewer concerns about pain and pain medications (P = 0.008), and lower patient pain over the past week (P = 0.014) and trended toward improvement in most other areas under study. Exploratory analyses suggest that EMPOWER had a greater effect for black subjects (vs. whites) on reducing concern about stigma. At three months, the intervention group trended better on most study outcomes. EMPOWER is a promising model to reduce barriers to pain management in hospice.